Pengaruh Kualitas Sistem Informasi Akademik terhadap Sikap serta Implikasinya pada Penggunaan Ulang - Boy Suzanto; S. Mia Lasmaya; Dhea Perdana Coenraad (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2017)
Academic information system is one of the information systems that can be applied in producing quality information so that it is expected to improve the quality of service for students and decision makers by stakeholder’s policy. This study intends to determine the effect of academic information system quality on the attitude and intention to use of students in colleges of High School of Economics in Bandung. The research method used survey of students by using first order structural equation modeling. The results showed that the quality of academic information system significantly influence the attitude and behavior of student reuse. The results of this study are expected to be useful for the development of science in the field of management, especially information systems management in universities.